Othering the minority: Comparative Study of Papua Ethnic in Indonesia and Rohingnya Ethnic In Myanmar During Military Rule - Insan Praditya Anugrah (Journal of Indonesian Social Sciences and Humanities, 2019)
The paper examines the comparative study of subaltern between Papua in Indonesia’s New Order era and Rohingya in Myanmar during military rule. In Indonesia, the Papuan case is an example of how the centralistic military regime treats Papuan ethnic as an object and treats them as “the others” rather than considers them as a part of the “Indonesian entity” as the subject itself. Meanwhile, in Myanmar, Rohingya case is an example of how the centralistic military junta regime treats Rohingya ethnic as “the others” and considers them as foreigners in Myanmar. This paper found a significant difference between the treatment of the Indonesian military regime towards Papuan ethnic and the treatment of the Myanmar military junta regime towards Rohingya ethnic. In Indonesia, the military regime acknowledges Papuan as a citizen of Indonesia. However, the regime considers Papuan as the “different other” nonetheless. Their different race and ethnicity from Java and Malay ethnic as the majority ethnic are not the subjects of the cause, yet it is caused by Papuan traditional behavior which is regarded as “backward” as by the central regime. Meanwhile in Myanmar, since the enforcement of citizenship law in 1982, the military regime clearly does not acknowledge Rohingya from state citizenship because of their identities, such as religion and Rohingya's historical background.